Social Media and Body Image Dissatisfaction Among Teen Athletes: A Qualitative Study - Yagin, Fatma Hilal; Flucus, Gheorghe (AI and Tech in Behavioral and Social Sciences, 2025)
This qualitative study examines the relationship between social media use and body image dissatisfaction among adolescent athletes, focusing on how digital exposure influences self-perception and psychological well-being in sports contexts. In-depth semi-structured interviews were conducted with 45 competitive teen athletes (ages 14-18) representing aesthetic (e.g., gymnastics) and non-aesthetic (e.g., soccer) sports. Participants were recruited from urban sports clubs, and data were analyzed through thematic analysis to identify patterns in social media engagement, body comparison behaviors, and emotional responses. Four key themes emerged: pervasive exposure to idealized athletic bodies (70% spent >2 hours/day on Instagram/TikTok), internalization of sport-specific body ideals (65% reported compulsive body-checking), cyberbullying (40% received critical comments about their physique), and variable coping strategies (only 20% actively curated positive content). Female athletes exhibited higher rates of dietary restriction, while males reported muscle-gaining pressures. Notably, 35% engaged in photo editing to meet perceived athletic standards. Social media exacerbates body image dissatisfaction among teen athletes by reinforcing unattainable ideals and sport-specific appearance pressures. These findings highlight the need for targeted interventions, including platform algorithms that limit harmful content, coach-led media literacy programs, and clinical screening tools adapted for athletic populations. Future research should explore longitudinal effects and platform-specific interventions.